The productivity myth in furniture manufacturing - Ratnasingam, Jegatheswaran; Reid, H. F. (Maney Publishing, 1996)
The purpose of this paper is to highlight the problems of productivity which face the European furniture manufacturers and in particular those based in the United Kingdom. It addresses the threats faced by the furniture industry, in light of escalating costs, from a productivity perspective. The paper sets out to suggest that contrary to common belief, productivity improvement is often related to an industrial infrastructure as exemplified by the Taiwanese furniture manufacturers.